Evaluating the Effectiveness of Targeted Interventions on the Quality of Life for Patients with Ischemic Stroke - Sultanah Al Harbi; Mohammed Al Ghetami; Mohamed Ahmed; Mohammed Al Althobaiti; Ahmed Newera; Hadeel Al Talhi; Fatmah Alzobidi; Frenk Lee Baldovino; Kamille Bianca Raviz; Leo Medalla; Andyson Mocorro (Global Journal on Quality and Safety in Healthcare)
Introduction Stroke is a prevalent health issue that poses substantial challenges for individuals and healthcare providers alike. It not only results in physical disabilities but also significantly affects the overall quality of life (QoL) for stroke survivors. Addressing these challenges necessitates a comprehensive approach that prioritizes improving functional abilities, fostering independence, and enhancing overall well-being of stroke survivors. A critical issue was observed at Al Hada Armed Forces Hospital (Taif, Saudi Arabia), where the average modified Rankin Scale (mRS) score for ischemic stroke survivors was estimated at 3.33, reflecting a poor QoL in terms of holistic limitations and, more importantly, limitations in daily activities. Methods This improvement project, conducted from May 2022 to July 2023, focused on establishing a comprehensive case management approach for patients with ischemic stroke, involving evidence-based best practices. The study was conducted in three phases: performing a literature review, development of an intervention protocol, and implementation and evaluation to assess feasibility and effectiveness. The evaluation used a quasi-experimental preintervention and postintervention evaluation approach, with qualitative data assessing the effect of the case management strategies on patient QoL as well as qualitative data estimating patient compliance and satisfaction. Results The target population of the study consisted of 136 patients diagnosed with ischemic stroke. This project yielded significant improvements in the QoL of patients with ischemic stroke, evident by the reduction in the average mRS score from 3.33 to 0.91 (p < 0.001). The effective implementation of case management services also had a positive effect on postdischarge patient satisfaction, which rose from 45% to 94%, as well as on readmission rates secondary to stroke, reduced from an average of 6.2% to 4%. Additionally, improving the QoL of patients with ischemic stroke resulted in a gain of approximately 0.41 quality-adjusted life-years per patient, with estimated cost savings of 76,897–153,794 Saudi riyals (20,467–40,935 US dollars [USD]). Conclusion This study highlights the effectiveness of an evidence-based case management intervention in improving outcomes for individuals facing poststroke challenges. Our findings support the importance of case management–based interventions in addressing the unique needs of this population.